Improving of Rice Blast Resistances in Japonica by Pyramiding Major R Genes - Xiao, Ning; Wu, Yunyu; Pan, Cunhong; Yu, Ling; Chen, Yu; Liu, Guangqing; Li, Yuhong; Zhang, Xiaoxiang; Wang, Zhiping; Dai, Zhengyuan; Liang, Chengzhi; Li, Aihong (Frontiers in Plant Science, 2017)
Rice blast, caused by the fungal pathogen Magnaporthe oryzae, is a major constraint to rice production worldwide. In this study, we developed monogenic near-isogenic lines (NILs) NILPi9, NILPizt and NILPi54 carrying genes Pi9, Pizt and Pi54, respectively, by marker assisted backcross breeding (MABB) using 07GY31 as the japonica genetic background with good agronomic traits. Polygene pyramid lines (PPLs) PPLPi9+Pi54 combining Pi9 with Pi54, and PPLPizt+Pi54 combining Pizt with Pi54 were then developed using corresponding NILs with genetic background recovery rates of more than 97%. Compared to 07GY31, the above NILs and PPLs exhibited significantly enhanced resistance frequencies (RFs) for both leaf and panicle blasts. RFs of both PPLs for leaf blast were somewhat higher than those of their own parental NILs, respectively, and PPLPizt+Pi54 exhibited higher RF for panicle blast than NILPizt and NILPi54 (P<0.001), hinting an additive effect on the resistance. However, PPLPi9+Pi54 exhibited lower RF for panicle blast than NILPi9 (P<0.001), failing to realize an additive effect. PPLPizt+Pi54 showed higher resistant level for panicle blast and better additive effects on the resistance than PPLPi9+Pi54. It was suggested that major R genes interacted with each other in a way more complex than additive effect in determining panicle blast resistance levels. Genotyping by sequencing (GBS) analysis and extreme-phenotype genome-wide association study (XP-GWAS) further confirmed the above results. Moreover, data showed that pyramiding multiple resistance genes did not affect the performance of basic agronomic traits. So the way to enhance levels of leaf and panicle blast resistances for rice breeding in this study is effective and may serve as a reference for breeders.